Evaluation of user experience: a systematic literature review - Syahrozad Najwa Fionillah; Subriadi Apol Pribadi (E3S Web of Conferences, 2024)
System evaluation research on user experience applied in using mobile applications. Systematic review of papers taken from the last 6 years, papers published in conference publications or journals, and papers available in English. The strategy used in searching for 30 articles was to create research questions, search for keywords appropriate to the topic, carry out inclusion and exclusion and ensure the quality of the paper assessment. From various studies that evaluate application user experience, I found that there are many factors that have not been fully successful, so researchers use the questionnaire method more because they think this method is easier to reach users widely. This literature review aims to explore users’ experiences with system services, and why users who are experienced with mobile applications are likely to continue using those applications. This systematic review is a methodology for identifying, evaluating, and defining relevant research on this topic answering several research questions and using a replicable and verifiable process that aims to find out what has not met user expectations. The main findings of this literature review are the percentage results of factors that influence user experience, techniques used to evaluate user experience and the benefits of evaluating user experience.